2020
DOI: 10.1021/acs.joc.0c00324
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of Iminosugar 2-Deoxy(thio)glycosides from Bicyclic Iminoglycal Carbamates Promoted by Cerium(IV) Ammonium Nitrate and Cooperative Brønsted Acid-Type Organocatalysis

Abstract: The first examples of iminosugar-type 2-deoxy(thio)glycoside mimetics are reported. The key step is the activation of a bicyclic iminoglycal carbamate to generate a highly reactive acyliminium cation. Cerium(IV) ammonium nitrate efficiently promoted the formation of 2-deoxy S-glycosides in the presence of thiols, probably by in situ generation of catalytic HNO3, with complete α-stereoselectivity. Cooperative phosphoric acid/Schreiner's thiourea organocatalysis proved better suited for generating 2-deoxy Oglyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…The ensemble of data collected on the immunomodulatory behavior of sp 2 -IGLs [45][46][47][48][49][50][51][52][53][54][55] instils that linear aliphatic tails with a length equal or higher than C 8 are required to elicit significant anticancer, antiparasitic and/or anti-inflammatory responses. Accordingly, we focused on n-octyl and n-docecyl aglycone lipid tails in this study.…”
Section: Design and Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…The ensemble of data collected on the immunomodulatory behavior of sp 2 -IGLs [45][46][47][48][49][50][51][52][53][54][55] instils that linear aliphatic tails with a length equal or higher than C 8 are required to elicit significant anticancer, antiparasitic and/or anti-inflammatory responses. Accordingly, we focused on n-octyl and n-docecyl aglycone lipid tails in this study.…”
Section: Design and Synthesismentioning
confidence: 99%
“…1 H NMR (300 MHz, CD 3 OD): δ 4.63 (d, 1 H, J 1,2 = 5.1 Hz, H-1), 4.48 (t, 1 H, J 6a,6b = J 5,6a = 8.5 Hz, H-6a), 4.27 (dd, 1 H, J 5,6b = 4.8 Hz, H-6b), 3.82 (ddd, 1 H, J 4,5 = 9.5 Hz, H-5), 3.61 (t, 1 H, J 2,3 = J 3,4 = 9.5 Hz, H-3), 3.47 (dd, 1 H, H-2), 3.26 (t, 1 H, H-4), 2.63-2.53 (m, 2 H, NHCH 2 ), 1.58-1.20 (m, 20 H, CH 2 ), 0.90 (t, 3 H, 3 J H,H = 6.9 Hz, CH 3 ). 13 C NMR (75.5 MHz, CD 3 OD): δ 159.2 (CO), 75.6 (C-4), 74.5 (C-3), 72.3 (C-2), 69.6 (C-1), 67.9 (C-6), 54 To a stirred solution of (1R)-1,2,3,4-tetra-O-acetyl-5N,6O-oxomethylidenenojirimycin (16) (150 mg, 0.40 mmol) in anhydrous DCM (8 mL) under Ar atmosphere, the corresponding selenol (0.84 mmol, 2.1 equiv.) and BF 3 .Et 2 O (0.18 mL, 1.41 mmol, 3.5 equiv.)…”
Section: Procedures For the Synthesis Of Pseudo-n-glycoside (12)mentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have previously shown that replacing the amine-type endocyclic nitrogen atom in iminosugar frameworks by a pseudoamide-type nitrogen (sp 2 -iminosugars) represents a versatile strategy to achieve highly selective glycosidase ligands for fundamental studies on enzyme mechanisms 40–43 and drug discovery, with applications ranging from cancer 44–46 and inflammation 47 to antiparasitic agents 48 . sp 2 -iminosugars are very well adapted to molecular diversity schemes, including modifications in the configurational pattern, the heterocycle framework and the nature of substituents 49–53 . Their outstanding chemical flexibility is ideally suited for structure-activity relationship studies, which has allowed optimising candidates capable of restoring the correct folding and trafficking of several LSD-causative mutant glycosidases.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, the successful preparation of these medium-sized guanidines demonstrates the robust versatility and novelty of the β-ARF/cyclization protocol, enabling the synthesis of polyhydroxylated nitrogen-containing cyclic structures otherwise difficult to access by any reported method to date. It should also be noted that the methodology described herein is one of the few general existing methods for the formation of exo- and endoguanidine sugars presenting oxidation at the pseudoanomeric position, which gives these compounds a greater degree of sugar character and could potentially permit subsequent derivatization through this hemiaminal-like center …”
mentioning
confidence: 99%